„Wieszcz negacji ” i „pobożna heretyczka”. Przemyślenia w zibaldonowym stylu wokół nieznanego tropu recepcji Leopardiego w Niemczech - Czajka, Anna (Colloquia Litteraria, 2023)
The text in zibaldon’s multi-discursive style presents hitherto unexplored moments of influence of Leopardi’s work in its transmission to German culture. It focuses on the acquisition and transformation of the poetic message of the Italian in the work of the poet and philosopher Margarete Susman, the result of which is to perceive poetry as penetrating philosophy and opening access to the Mystery of Being (Susman, then Heidegger, Gadamer).